Marine fish farming in Malta: Strategies and development - Agius C. (Mediterranean offshore mariculture, 2000)
In small island states of subtropical and tropical latitudes, shortage of space and fresh water as well as competition for these scarce resources from other economic sectors such as tourism usually limits the potential for aquafarming to the marine environment. Moreover, these more lucrative sectors usually force aquaculture away from the prime foreshore sites out into the more exposed waters. Modern technology has come up with very practical and reliable, commercial scale cage structures for offshore sites. Increasingly sophisticated equipment such as for feeding, grading and harvesting have made life easier out at sea and have made possible the strict control over all activities concerned.
Advanced Course of the CIHEAM Network on Technology of Aquaculture in the Mediterranean on 'Mediterranean Offshore Mariculture', 1997/10/20-24, Zaragoza (Spain)